1994
DOI: 10.1161/01.str.25.10.1924
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of plasma homocyst(e)ine and risk of ischemic stroke.

Abstract: Background and Purpose Several studies have reported elevated circulating homocyst(e)ine levels in subjects with cerebral atherosclerosis. We assessed prospectively whether high plasma levels of homocyst(e)ine affect risk of ischemic stroke and evaluated whether high blood pressure modifies any such effect.Methods The study sample was drawn from the Physicians' Health Study, a randomized, double-blind, placebo-controlled trial of aspirin and beta-carotene in 22 071 US male physicians. A total of 14 916 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
1
15

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(201 citation statements)
references
References 31 publications
7
178
1
15
Order By: Relevance
“…For proponents of the homocysteinestroke hypothesis it was somewhat disconcerting that the two prospective studies included in this meta-analysis, both based on a nested case-control design, were negative. 18,19 In the US physicians study a weak non-significant association was observed between total homocysteine concentrations and ischaemic stroke 19 and in a propective study from the North Karelia Project, no association with either myocardial infarction or stroke was observed. 18 It should be emphasised however that these studies may have lacked power to address the homocysteine-stroke hypothesis as both were based on populations with relatively few individuals in the upper tail of the skewed tHcy distribution.…”
Section: Thcy and Strokementioning
confidence: 98%
See 1 more Smart Citation
“…For proponents of the homocysteinestroke hypothesis it was somewhat disconcerting that the two prospective studies included in this meta-analysis, both based on a nested case-control design, were negative. 18,19 In the US physicians study a weak non-significant association was observed between total homocysteine concentrations and ischaemic stroke 19 and in a propective study from the North Karelia Project, no association with either myocardial infarction or stroke was observed. 18 It should be emphasised however that these studies may have lacked power to address the homocysteine-stroke hypothesis as both were based on populations with relatively few individuals in the upper tail of the skewed tHcy distribution.…”
Section: Thcy and Strokementioning
confidence: 98%
“…13 There are additional concerns regarding unmeasured and residual confounding due to dietary and other lifestyle factors associated with hyperhomocysteinaemia. 14,15 The findings from the small number of prospective studies that have addressed associations between tHcy concentrations and incident coronary heart diseases (CHD) or stroke are inconsistent [16][17][18][19][20][21][22] Homozygosity for a defective thermolabile variant of MTHFR, a common genetic polymorphism which results in hyperhomocysteinemia, has not been consistently linked with cardiovascular disease endpoints. 23,24 Although the importance of gene markers will vary depending on relevant environmental exposures, diet in this instance, the findings from gene association studies conducted to-date are distinctly unimpressive.…”
Section: Thcy and Cardiovascular Diseasementioning
confidence: 99%
“…This association has been con®rmed in some, but not in all prospective studies (Stampfer et al, 1992;Verhoef et al, 1994;Perry et al, 1995;Arnesen et al, 1995;Folsom et al, 1998;Wald et al, 1998;Alfthan et al, 1994;Evans et al, 1997). In a cross-country study with WHO MONICA data (Alfthan et al, 1997) high plasma tHcy concentrations were associated with increased cardiovascular mortality, and both the mean plasma tHcy concentration and cardiovascular mortality were the highest in Finland.…”
Section: Introductionmentioning
confidence: 96%
“…Several prospective studies of white subjects showed a significant association between homocysteine and the risk of total 4 -8 and ischemic strokes, 8 whereas others showed no association. 9,10 There have been no prospective studies of the effect of homocysteine on the risk of stroke in Asian populations. 11 Furthermore, only one prospective study among whites has reported the association between homocysteine levels and the age-and sex-adjusted risk of stroke subtypes; that study suggested that hyperhomocysteinemia was more predictive of risk for lacunar infarction than other stroke subtypes.…”
mentioning
confidence: 99%